Collaboration in Inclusive Education - Biran, Megaiswari (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2023)
The implementation of inclusive education is a strategy to accelerate the nine-year compulsory education including children with special needs. The implementation has become good news for children with special needs as they can have options of schools. Collaboration is important to achieve an inclusive environment in inclusive education. Inclusive education means every child that learns and every adult who works in the environment is accepted, appreciated, and accommodated. Collaboration between teachers and the family of children with special needs is essential to support students’ learning activity and secure the necessary accommodation. The collaboration between teachers and the family concerns the students’ needs, goals, program, and their development, as well as provides information on their children’s learning process. Headmaster holds power and authority in building and directing an inclusive environment. Nevertheless, the success of inclusive education depends on collective responsibility that can only be achieved with the collaboration of schools, professionals, parents, and government. This research was conducted using study literature.